Focal atrophy of the masticatory muscles caused by pure trigeminal motor neuropathy: case report. Issue 1 (January 2016) - Wilson, M.H.; Hodgson, E.J.; Felstead, A.M.
Abstract: Pure trigeminal motor neuropathy is rare and characterised by weakness of the mandibular motor branch with no signs of involvement of the trigeminal sensory or other cranial nerve. Its aetiology is unclear but it has been hypothesised that a viral infection may be a cause. Magnetic resonance imaging is useful in its diagnosis and typically shows loss of volume of the affected masticatory muscles and infiltration of fat. We describe the case of a 29-year-old woman who presented with a 12-year history of progressive facial asymmetry, which was later shown on imaging to be caused by unilateral atrophy of the masseter with compensatory contralateral hypertrophy.